Nurses' knowledge and attitudes regarding malnutrition in children and its management in Ghana - Victor Mogre; Alaru Yakubu; Musah Fuseini; Anthony Amalba; Sixtus Aguree (AOSIS, 2017)
Background: Malnutrition contributes significantly to child morbidity and mortality. Nurses require appropriate knowledge, skills and attitudes to prevent and treat malnutrition in children using appropriate guidelines or protocols. Objectives: The aim of this article was to assess nurses' knowledge, attitudes towards malnutrition and its management using the World Health Organization (WHO) or United Nations International Children's Fund guidelines for the treatment of severely malnourished children and to evaluate factors associated with their knowledge and attitudes. Methods: Participants included 104 nurses working in the outpatient and paediatric units or departments of four hospitals in Tamale metropolis. An 88-item questionnaire was used to measure nurses' socio-demographic characteristics as well as their knowledge and attitudes towards malnutrition in children and its management using the WHO guidelines for the inpatient treatment of severely malnourished children. Results: Nurses' knowledge in malnutrition and its management was slightly above average (54.0%), but their attitudes were highly positive. Factors that were associated with nurses' knowledge were number of nutrition courses undertaken in nursing school, number of years working as a nurse, receipt of a refresher course on nutrition after school and receipt of training on the guidelines. Nurses' attitudes were associated with report of having awareness on the guidelines, number of years a nurse has been involved in the treatment of a severely malnourished child. Conclusion: Nurses' knowledge levels in the inpatient treatment of severely malnourished children were not desirable. However, their attitudes were generally positive. Receipt of previous training, awareness of the WHO guidelines, practice experience and number of years as a nurse significantly affected knowledge and attitude scores in the positive direction.